Comparison of Hydraulic Fracturing and Deflagration Fracturing Under High-Temperature Conditions in Large-Sized Granite - Hengtao Yang; Yan Zou; Bing Bai; Huiling Ci; Tiancheng Zhang; Zhiwei Zheng; Hongwu Lei (Applied Sciences)
Fracturing is an indispensable technique in geothermal energy development. Large-sized model tests of different fracturing methods are crucial for evaluating the fracturing effect and extrapolating the results to field applications. For common hydraulic and deflagration fracturing methods, 40 × 40 × 40 cm3 granite samples were used to carry out fracturing tests under high-temperature conditions in this paper. Through the analysis of the fracturing parameters and multiscale fracture morphology, a series of key findings were summarized. Deflagration fracturing is more intense, notably unaffected by the principal stress difference, and is capable of generating fracture spaces tens of times larger than those created by hydraulic fracturing. Furthermore, high temperatures tend to produce more fracture zones rather than continuous cracks during hydraulic fracturing. In contrast, deflagration fracturing yields simpler and more regular fractures in granite at high temperatures. Finally, the influence of the borehole number and the quantity of the deflagration agent on the fracturing effect are briefly discussed. These findings provide valuable insights for enhancing reservoir stimulation in geothermal systems.